Resolubilidade local para duas classes de campos de vetores suaves complexos - Nunes, Luciele Rodrigues (Universidade Federal de São Carlos, 2016)
This work study complex linear partial differential operators of order one without having terms of zero order (complex vector fields). We have established a necessary and suficient condition for local solvability of a class of operators which are not elliptic precisely in a 1-dimensional submanifold and we construct solutions for a class of operators satisfying the condition (P) and which are not elliptic precisely in a point.
Keywords: Equações diferenciais parciais; Campos de vetores complexos suaves; Resolubilidade local; Operadores do tipo mizohata; CIENCIAS EXATAS E DA TERRA::MATEMATICA